PERKEMBANGAN GEREJA KATOLIK ST.THERESIA LISIEUX DI KOTA SIBOLGA TAHUN 1932-2008 - Maria, Sylvia; Lukitoyo, Pristi Suhendro; Muris, Dwiki Pamungkas; Salsabil, Tiara (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
Regarding the background of the establishment of the Catholic Church of ST. Theresia Lisieux was started when the mission of the Catholic Church began in the last century, when colonialism reached its peak and modern capitalism began to exist in this region, since the arrival of Fr. Chrysologus Timmermans from Sevenbergen came to the Sibolga region to carry out missions in establishing the parish of Sibolga. The development of the founding of the Catholic Church of ST. Theresa Lisieux can be seen from the increase in the number of Catholics in the Catholic Church of ST. Theresa Lisieux, from 70 Catholics in 1932 to 208,212 at the end of 2008. And the development of the founding of the Catholic Church of ST. Theresa can also be seen from this church building which was originally a house purchased by Father Timmermans which was originally used as a chapel as a place of worship in 1929, and in 1932 the Church building was built. The existence of the Catholic Church of ST. Theresia Lisieux in Sibolga City has a positive impact on Catholics. The impact of the establishment of the Catholic Church is covering the fields of education, social, and economic. In the field of education, namely the establishment of People's Schools, kindergartens, elementary schools, junior high schools, and high schools, which were founded by sisters sent by missionaries. In the social sector, namely Visiting FKUB Sibolga City, OMK Solidarity Action sharing with the Elderly, Gotong Royong welcoming the birthday of the Cathedral. In the economic sector, there are CU Sejati and Efata Shopp services in the church environment.